Meningkatkan Efektivitas Penulisan Ilmiah melalui Mendeley Reference Manager - Patrisia Rahayu Utami; Imran, Imran; Iwan Ramadhan; Fauziah Sri Wahyuni; Muhammad Nur Imanulyaqin (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to increase the effectiveness of students' scientific writing through training in the use of Mendeley Reference Manager. The training was conducted for 10 students of the Tanjungpura University Sociology Education Study Program using lecture and hands-on methods which included delivering material through presentations, practicing the installation and use of Mendeley features, as well as discussion and mentoring. The method used is field research as a qualitative descriptive research. Data collection techniques were participant observation, questionnaires and documentation. Data sources came from primary and secondary data. The results of the activity showed 90% of participants successfully used Mendeley to manage references and organize citations automatically, improving the quality and consistency of their scientific writing. Evaluation through pre-test showed 10% of participants had excellent understanding, 40% good, 10% fair, and 40% poor. After the training, the post-test showed improvement, with 50% of participants feeling very satisfied, 40% satisfied, and 10% moderately satisfied. This activity proves that Mendeley training is effective in reducing citation format errors and the risk of plagiarism, as well as encouraging a better academic culture.